Psychological and sociological determinants of entrepreneurial intentions and behaviors - Antončič, Boštjan; Auer Antončič, Jasna (Frontiers in Psychology, 2023)
Research concerned with the personality of entrepreneurs entails an important part of the research into the management of small and medium-sized enterprises and entrepreneurship. This research has added new knowledge about the role of entrepreneurs’ personality characteristics, their family entrepreneurial background, and the local supportive entrepreneurial background in entrepreneurial start-up intentions and behaviors. Hypotheses and a model were developed and verified using structural equation modeling and regression analysis considering data from a sample of entrepreneurs and students. This research revealed that several personality and sociological factors can be important for entrepreneurship when it comes to starting a business. The most important were the Big Five personality factors openness, extraversion, and non-agreeableness and, to a smaller extent, emotional stability (non-neuroticism) and conscientiousness. The second-most important group of factors were the specific motivational characteristics entrepreneurial self-efficacy, internal locus of control, and risk-taking propensity. Sociological factors were much less important than psychological elements for establishing business.